2019
DOI: 10.3791/59706
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Monocyte Chemotactic Activity In Vivo and Characterization of Blood Monocyte Derived Macrophages

Abstract: Tissue homeostasis and repair are critically dependent on the recruitment of monocyte-derived macrophages. Both under-and over-recruitment of monocyte-derived macrophages can impair wound healing. We showed that high fat and high sugar diets promote monocyte priming and dysfunction, converting healthy blood monocytes into a hyper chemotactic phenotype poised to differentiate into macrophages with dysregulated activation profiles and impaired phenotypic plasticity. The over-recruitment of monocyte-derived macro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…It has been reported that mechanically ventilated patients who developed ventilator-associated pneumonia had significant higher levels of MCP-1 (P<0.05) compared with patients who developed ventilator pneumonia for the purpose of developing ventilator pneumonia. Further analysis in the study revealed that when patients with ventilator pneumonia progressed to respiratory distress syndrome, the levels of MCP-1 again showed a significant elevation compared with patients who did not develop respiratory distress syndrome [17][18][19]. Several studies have pointed out that plasma MCP-1 levels can be used as a biomarker for predicting organ dysfunction, organ failure, and mortality in patients with sepsis, as well as for the diagnosis of sepsis [20,21].…”
Section: Analysis Of Wbc Crp Pct Smr and Mcp-1 Levels In Children Wit...mentioning
confidence: 98%
“…It has been reported that mechanically ventilated patients who developed ventilator-associated pneumonia had significant higher levels of MCP-1 (P<0.05) compared with patients who developed ventilator pneumonia for the purpose of developing ventilator pneumonia. Further analysis in the study revealed that when patients with ventilator pneumonia progressed to respiratory distress syndrome, the levels of MCP-1 again showed a significant elevation compared with patients who did not develop respiratory distress syndrome [17][18][19]. Several studies have pointed out that plasma MCP-1 levels can be used as a biomarker for predicting organ dysfunction, organ failure, and mortality in patients with sepsis, as well as for the diagnosis of sepsis [20,21].…”
Section: Analysis Of Wbc Crp Pct Smr and Mcp-1 Levels In Children Wit...mentioning
confidence: 98%